Dieta natural de Macrobrachium amazonicum (Heller, 1862) (Crustacea, Decapoda) no Oeste de Minas Gerais, Brasil - Mulati, Ana Laura Lima (2017)
Natural food is interlinked with various factors affecting populations, such as predation, interactions within food webs, reproduction, nutrition, etc. Studies that contemplate this theme are very important to obtain knowledge about the ecology and conservation of the species. The knowledge about the natural diet of a population provides subsidies for the adequate management of fished species, as is the case of shrimp Macrobrachium amazonicum, the target of the studies in this work. One means of evaluating the natural diet of a species is by means of the stomach contents. The objective of this work was to evaluate the natural diet of the M. amazonicum sweet shrimp species, to verify differences in male and female feeding, the relation of the consumed items with the abiotic factors and to analyze the relation between the consumed items and the length of the Cephalothorax between males and females. The animals were collected in Lagoa da Mangueira, a natural environment in the municipality of Perdões, in the west of Minas Gerais. The collections were carried out between August 2013 and May 2014. The animals were collected in 15 sieves, placed in a thermal box with ice and later fixed in 70% alcohol. In the laboratory, the animals were sexed and the length of the cephalothorax was measured. The stomachs were removed and their contents analyzed under stereomicroscope microscope. To analyze the data, a Wincoxon test was performed to verify if there were differences between males and females, between food items and the indexes used. A linear regression was performed to check if there was a relationship between abiotic factors and food items, and length of cephalothorax and food items. In all analyzes, food items were used as response variables and indices, cephalothorax length and abiotic variables as predictor variables. The main items found were digested material, plant material, stone, sand, spike, exoskeleton, Neuroptera, Trichoptera, Plecoptera and Diptera. The Wilcoxon test did not show significant differences between male and female feeding except for the spike and Trichoptera items. There was also no difference between the food items and the indices used. The linear regression showed that for the abiotic factors conductivity, oxygen and pH there are positive and negative relations with some of the food items found. The only food item related to the length of cephalothorax in males and females was digested material. The results show that abiotic factors should be taken into account in ecological studies with prawns of the genus Macrobrachium because they are important factors in feeding these crustaceans. In addition, the preservation of environments such as Mangueira Lagoon should be evaluated so that more studies can be carried out and more information acquired about the Brazilian shrimp species.